PSX-39 Effect of body condition measured using a sow caliper on performance of group-housed gestating sows. (7th December 2018) - Li, Y; Cui, S; Baidoo, S; Johnston, L
Abstract: This study was designed to evaluate an optimal range of caliper measurements for sows to achieve acceptable performance. Pregnant sows (n=928, Parity 1–9) were housed in pens (42–51 sows/pen) with an electronic sow feeder at wk-5 postmating and remained until d-109 of gestation. Sows farrowed in stalls and weaned their litters about 18 d after farrowing. Sows that were mated within one week after weaning were considered having completed the study. Sow caliper measurements were recorded at the P2 location and backfat depth using an ultrasonic scanner was recorded at the same location on both sides of the body. A scoring system of 1 (emaciated) to 5 (obese) was used for visual assessment of body condition. At exit of gestation pens, 10% of sows across parities had caliper measurements between 14.5 and 18.0 (Fat), 55% of sows between 10.5 and 14.0 (Fit), 20% of sows between 8.5 and 10.0 (Thin), and 15% of sows between 4.0 and 8.0 (Very-Thin). Correlation coefficients (r) of caliper measurements with ultrasonic backfat depth measurements and visual scores were 0.714 and 0.665 (both P<0.0001), respectively. Very-Thin old sows (parity 7–9) gained less weight (23.7 vs. 30.3 kg, SE=1.82; P<0.05) in gestation pens, and Fat old sows had lower completion rate (36% vs. 72.5%, Chi-square=30.6; P<0.0001) than Fit and Thin sows within the same parity category. Across parities, Very-Thin sows had lower farrowing rate (64% vs. 98%, Chi-square=239.8; P<0.0001) and completion rate (49% vs. 87%, Chi-square=128.7; P<0.0001) compared with other sows. Caliper measurements did not affect (all P>0.11) litter size farrowed (live born=13.2 ± 0.39, 12.3 ± 0.16, 12.5 ± 0.26, and 12.5 ± 0.38 for Fat, Fit, Thin, and Very-Thin sows, respectively) or weaned (10.5 ± 0.35, 10.3 ± 0.14, 10.4 ± 0.24, and 10.2 ± 0.35). These results suggest that sows across parities with caliper measurements between 8.5 and 14.0 had acceptable performance in the current study. Key Words: